2002
DOI: 10.5194/npg-9-477-2002
|View full text |Cite
|
Sign up to set email alerts
|

Neural-network-based prediction techniques for single station modeling and regional mapping of the <I>fo</I>F2 and M(3000)F2 ionospheric characteristics

Abstract: Abstract. In this work, Neural-Network-based single-station hourly daily foF2 and M(3000)F2 modelling of 15 European ionospheric stations is investigated. The data used are neural networks and hourly daily values from the period 1964-1988 for training the neural networks and from the period 1989-1994 for checking the prediction accuracy. Two types of models are presented for the F2-layer critical frequency prediction and two for the propagation factor M(3000)F2. The first foF2 model employs the E-layer local n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Xenos (2002) demonstrated the NN technique for single station modelling and regional mapping of M(3000)F2 in the European region.…”
Section: M Hoque and N Jakowski: A New Global Model For The Ionomentioning
confidence: 99%
“…Xenos (2002) demonstrated the NN technique for single station modelling and regional mapping of M(3000)F2 in the European region.…”
Section: M Hoque and N Jakowski: A New Global Model For The Ionomentioning
confidence: 99%
“…This has been described by several authors (Williscroft and Poole, 1996;Tulunay et al, 2000;Poole and Poole, 2002). Several other authors have also employed the use of two hidden layers based on the complexity of their networks (Mehrotra et al, 1991;Lamming and Cander, 1999;Derong et al, 2002;Xenos, 2002). On this note, two hidden layers are employed in this work based on the observations that it learned faster and performed better than one hidden layer on the basis of their RMS errors.…”
Section: Neural Network Configurationmentioning
confidence: 98%
“…The application of neural networks (NNs) is generally motivated by its principal ability to generalize from a set of training patterns. Several authors have demonstrated that NNs can be used to describe nonlinear phenomena (Wu and Lundstedt, 1996;Williscroft and Poole, 1996;Altinay et al, 1997;Kumluca et al, 1999;Wintoft and Gander, 0273-1177 , 2000Zakharov and Tyrnov, 1999;Mckinnell and Poole, 2000;Xenos, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…been frequently used in single-station ionospheric empirical models [Francis et al, 2001;Huang and Yuan, 2014;Oyeyemi et al, 2005;Tulunay et al, 2006;Xenos, 2002].…”
Section: 1002/2016rs006171mentioning
confidence: 99%
“…However, few studies on single‐station TEC empirical models using the nonlinear least squares fitting method have been conducted. Other methods, such as neural networks, have been frequently used in single‐station ionospheric empirical models [ Francis et al , ; Huang and Yuan , ; Oyeyemi et al , ; Tulunay et al , ; Xenos , ].…”
Section: Introductionmentioning
confidence: 99%